1993
DOI: 10.1515/znc-1993-5-604
|View full text |Cite
|
Sign up to set email alerts
|

Rare Flavonoid Aglycones from Anaphalis margaritacea and Two Gnaphalium Species

Abstract: In stitu t für B otanik der T echnischen H ochschule, S ch n ittsp ah n straß e 3, D-W -6100 D arm sta d t, B undesrepublik D eutschland J. Jakupovic Institut für O rganische Chem ie, FB-5, T echnische U n iv ersität Berlin, Straße des 17. Juni 135,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Merrill was found to excrete the flavone luteolin-3'-Me and several flavonols: galangin, gal-3-Me, gal-7-Me, kaempferol, 8-OH-galangin-8-Me, 8-OH-gal-3,8-diMe, quercetin-3-Me, and qu-3,3'-diMe. Due to the presence of galangin and its derivatives as well as of 8-O-substituted flavonols the flavonoid pattern of this species is similar to those observed in Gnaphalium species, in Cassinia quinquefaria and in Anaphalis margaritacea (Wollenweber et al, 1993a, b).…”
Section: Gnaphalieaesupporting
confidence: 74%
“…Merrill was found to excrete the flavone luteolin-3'-Me and several flavonols: galangin, gal-3-Me, gal-7-Me, kaempferol, 8-OH-galangin-8-Me, 8-OH-gal-3,8-diMe, quercetin-3-Me, and qu-3,3'-diMe. Due to the presence of galangin and its derivatives as well as of 8-O-substituted flavonols the flavonoid pattern of this species is similar to those observed in Gnaphalium species, in Cassinia quinquefaria and in Anaphalis margaritacea (Wollenweber et al, 1993a, b).…”
Section: Gnaphalieaesupporting
confidence: 74%
“…To date, 28 flavone derivatives, 1 – 28 , 37 flavonol derivatives, 29 – 65 , one flavanone, 66 , and two chalcone derivatives, 67 , 68 , have been reported, which constitute the majority of the secondary metabolites from the genus Gnaphalium [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48]. Among them, 28 compounds, 2 – 5 , 7 – 10 , 13 – 16 , 23 , 27 , 28 , 32 – 39 , 41 , 43 – 45 , and 68 , were isolated as O -glycosides.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…
We have carried out systematical phytochemical studies on several medicinal herbs used in traditional Tibetan medicine growing only at 2500-4000 m above sea level on Qinghai-Tibet Plateau and found that all these plants are abundant in flavonoids [1][2][3][4][5]. The genus Anaphalis (Compositae) is widely distributed in the west and southwest regions of China, and 17 species of them are used as medicinal plants.
…”
mentioning
confidence: 99%